Power distance: moderating effect on positive youth development in Malaysian co-curricular programs - Nouri, Katayoun Mehdinezhad; Krauss, Steven; Ismail, Ismi Arif; Arshad, Mohd Mursyid; Zaremohzzabieh, Zeinab (Elsevier, 2023)
Few studies have explored the effects of sociocultural factors on program quality in the context of positive youth development (PYD) programs. This is of relevance to countries known for high power distance between youth and adults. The current study explored the moderating effect of perceived power distance orientation on the relationship between youth program quality and the six C’s of PYD. A partial least square-structural equation modeling (PLS-SEM) was tested among 436 first-year undergraduate co-curricular program participants from public universities in Malaysia (M = 21.192 years, SD = 1.191 years; 65.6% female). Youth voice, supportive adult relationships, and program engagement positively predicted PYD, while feelings of safety did not. Power distance had no moderating effect on PYD. The findings extend support for the importance of program quality on PYD in non-WEIRD youth program settings and point to the need for further inquiry on PYD program practices in diverse sociocultural settings.